2013
DOI: 10.1002/jts.21785
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Posttraumatic Stress Disorder on Blood Pressure and Heart Rate in a Veteran Population

Abstract: Hyperarousal is a hallmark of posttraumatic stress disorder (PTSD). PTSD has been associated with increased blood pressure (BP) and heart rate (HR) in veteran populations. We retrospectively identified male patients consulted to outpatient psychiatry at the Iowa City Veterans Affairs Healthcare System. Patients were divided into PTSD (n = 88) and non-PTSD (n = 98) groups. All PTSD patients and a subset of non-PTSD patients had documented blast exposure during service. The study investigated whether patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 22 publications
2
50
2
Order By: Relevance
“…Measurement error due to under-reporting of risk behaviors could account for these findings, but they also suggest other mechanisms may play a role. For example, prior research found that PTSD increased the likelihood of hypertension among adult war veterans [3233] and non-veterans who experienced a traumatic event (e.g. 9/11).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement error due to under-reporting of risk behaviors could account for these findings, but they also suggest other mechanisms may play a role. For example, prior research found that PTSD increased the likelihood of hypertension among adult war veterans [3233] and non-veterans who experienced a traumatic event (e.g. 9/11).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD, the sentinel trauma-related disorder, has been tied to hypertension across numerous, and largely cross-sectional, studies (e.g., Abouzeid et al ., 2012; Cohen et al ., 2009; Davidson et al ., 1991; Glaesmer et al ., 2011; Kang et al ., 2006; Lauterbach et al ., 2005; O’Toole & Catts, 2008; Paulus et al ., 2013; Pietrzak et al ., 2011; Sareen et al ., 2007; Stein et al ., 2014). Additionally, rates of metabolic syndrome—a constellation of cardiometabolic risk factors that includes hypertension—have been elevated in those with (vs. without) PTSD (e.g., Bartoli et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, although PTSD is twice as common in women than in men (Kessler et al ., 1995), studies examining PTSD and hypertension in younger and middle-aged civilian women exposed to a range of traumas are generally lacking. Much research has been in predominantly male veteran samples (e.g., Abouzeid et al ., 2012; Kang et al ., 2006; O’Toole & Catts, 2008; Paulus et al ., 2013; Schnurr et al ., 2000; see Cohen et al ., 2009, for an exception). Several studies have also suggested that PTSD is linked to increased hypertension risk in civilians (e.g., Davidson et al ., 1991; Glaesmer et al ., 2011; Lauterbach et al ., 2005; Pietrzak et al ., 2011; Sareen et al ., 2007; Stein et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They support the idea that PTSD is associated with elevated psychophysiology (Pole, 2007). As mentioned before, hypertension is found in many PTSD patients (Paulus et al, 2013). Other biological factors have been intensely studied in PTSD and have been summarized in two expert's reviews Sherin and Nemeroff, 2011).…”
Section: Biological Factors In Ptsdmentioning
confidence: 54%
“…In addition, there is evidence it may increase the blood pressure and hypertension as a consequence of the arousal symptoms of this disorder (Paulus et al, 2013). Furthermore, evidence has accumulated that childhood and probably adult trauma can increase the risk of cognitive impairment in old age, leaving a higher prevalence of dementia in this group (Burri et al, 2013).…”
Section: Prevalence Comorbidity and Prognosismentioning
confidence: 99%